Receiver-Assisted Partial-Reliable Multimedia Multipathing Over Multi-Homed Wireless Networks - Cao, Yuanlong; Zeng, Li; Liu, Qinghua; Lei, Gang; Huang, Minghe; Wang, Hao (IEEE access, 2019)
With the advancement of multimedia technologies and driven by the ever-increasing user interests in the variety of multimedia applications, the content-rich multimedia streaming services tend to be the most attractive service in future Internet. The multipath TCP (MPTCP), which uses multiple paths for parallel transmission and bandwidth aggregation, is considered to be the most potential transfer mechanism to satisfy the specific requirements of multimedia transmission in a multi-homed wireless network environment. However, the fully-reliable transmission nature of MPTCP can cause an unnecessary retransmission of expired multimedia data, block message from handing over to upper layer, and thus degrade the user-perceived multimedia service quality. In this paper, we propose a receiver-centric partial-reliable multipath transport solution (referred to as rec PR-MPTCP) to support real-time Internet multimedia applications. In the rec PR-MPTCP, a partial reliability extension is presented which runs at receiver side in order to offer a partial reliability multipathing service for multimedia applications. In addition, a new one-way delay-based bandwidth aggregation method is included into the rec PR-MPTCP in order to reduce the receive buffer blocking problem in MPTCP and increase multimedia services performance. Simulation results show that rec PR-MPTCP outperforms the current MPTCP solutions in terms of throughput performance and user-perceived quality of service.